2018
DOI: 10.1016/j.nanoen.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Construction of self-powered cytosensing device based on ZnO nanodisks@g-C3N4 quantum dots and application in the detection of CCRF-CEM cells

Abstract: We herein report a self-powered and renewable cytosensing device based on ZnO nanodisks(NDs)@g-C3N4 quantum dots. The device features enhanced photoelectrochemical (PEC) activity compared to ZnO NDs or g-C3N4 QDs alone. The enhanced PEC ability is attributed to the synergistic effect of the high visible light sensitivity of g-C3N4 QDs and the staggered band alignment heterojunction structure with suitable band offset, which affords higher photoelectron transfer and separation efficiency. In addition, the hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 94 publications
1
31
0
Order By: Relevance
“…The g-C 3 N 4 /metal-based materials (metal or metal oxide) can be synthesized by different methods for use as biosensors. The application of g-C 3 N 4 /metal oxide composites, including g-C 3 N 4 /ZnO, [103] g-C 3 N 4 /ZnO nanotubes, [104] ZnO nanodisks/g-C 3 N 4 quantum dots, [105] g-C 3 N 4 /TiO 2 nanotubes, [106] g-C 3 N 4 /TiO 2 NPs, [107] g-C 3 N 4 /TiO 2 nanosheets [108] and g-C 3 N 4 /WO 3 NPs, have been studied for the detection of biological substances by incorporaiton into PEC biosensors. [109] Xi et al reported hierarchically structured ZnO hybridized with g-C 3 N 4 as a new material for the nonenzymatic PEC sensing of hydrogen peroxide (H 2 O 2 ).…”
Section: Photoelectrochemistry-based G-c 3 N 4 Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The g-C 3 N 4 /metal-based materials (metal or metal oxide) can be synthesized by different methods for use as biosensors. The application of g-C 3 N 4 /metal oxide composites, including g-C 3 N 4 /ZnO, [103] g-C 3 N 4 /ZnO nanotubes, [104] ZnO nanodisks/g-C 3 N 4 quantum dots, [105] g-C 3 N 4 /TiO 2 nanotubes, [106] g-C 3 N 4 /TiO 2 NPs, [107] g-C 3 N 4 /TiO 2 nanosheets [108] and g-C 3 N 4 /WO 3 NPs, have been studied for the detection of biological substances by incorporaiton into PEC biosensors. [109] Xi et al reported hierarchically structured ZnO hybridized with g-C 3 N 4 as a new material for the nonenzymatic PEC sensing of hydrogen peroxide (H 2 O 2 ).…”
Section: Photoelectrochemistry-based G-c 3 N 4 Biosensorsmentioning
confidence: 99%
“…[107] The as-prepared PEC aptasensor was used for the determination of shrimp tropomyosin in concentrations ranging from 1-400 ng Figure 7b) for the detection of CCRF-CEM cells. [105] Compared to ZnO NDs or g-C 3 N 4 QDs alone, the composites show enhanced PEC activity via the synergistic effect of the high visible-light sensitivity of the g-C 3 N 4 QDs and the staggered band alignment structure of the heterojunction with a suitable band offset, which enhances photoelectron transfer and the separation efficiency. f) The schematic illustration for fabrication of PEC aptasensor.…”
Section: Photoelectrochemistry-based G-c 3 N 4 Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of noble metals are relatively more expensive, which hamper the commercial application of the non -enzymatic glucose sensor. Thus, metal oxide based nanostructure is not only used in glucose sensor applications, but also applicable in the field of electrochemical immunosensor because of their lower cost, controllable synthesis, functional biocompatibility, chem- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 ical stability, enhanced electron-transfer kinetics, and strong glucose adsorption capabilities [26,28,[32][33][34][35][36][37]. Metal oxides such as CuO and Co 3 O 4 have established a great deal of attention owing to the environmentally friendly nature and relatively good conductivity, simple synthesis process, superior electrochemical property, and good chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, their PEC water oxidation efficiency still is severely limited by the large bandgap of 3.0 eV for rutile and 3.2 eV for anatase and the high recombination rate of photogenerated charge carriers . To address those obstacles, several strategies have been carried out to improve the PEC performance such as element doping, dye or inorganic sensitization, surface modification, and constructing heterostructure . Thereinto, introduction of visible light photosensitizer on TiO 2 ‐based to construct heterostructure is considered as a highly effective approach, which can not only extend the optical absorption edge of TiO 2 but also decrease the recombination rate of photogenerated electron‐hole pairs.…”
Section: Introductionmentioning
confidence: 99%